Baldassarre Fontana (1661-1733): some Notes and Considerations about Roman Languages in the Polish and Moravian Building Sites - Federico Bulfone Gransinigh (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2021)
This article analyzes the relationship between stucco decoration and architecture through the investigation of the languages used by Baldassarre Fontana, cousin of the more famous Carlo. The study of the stucco decoration and some architectures created by Baldassarre in Moravia and Poland will allow to underline the innovative elements in the languages used by the architect and plasterer of Chiasso, compared with roman examples including the altar of Santa Maria in Traspontina designed by Carlo Fontana or the chapel of Santa Cecilia in San Carlo ai Catinari and some works by Bernini. In Fontana’s work, the intention is to overturn the relationships between architecture and sculpture, in order to find the greatest possible separation between sculpture and architecture. Instead, in other yards, experimentation is already directed towards the rococò. The paper will consider some cases including the decoration of the church of Saint Anne in Krakow dated 1695-1704 and the low undercut plastic decoration made on the gothic vaults of the Zydowski palace, also in Krakow. The examples of the Wawrzyniec Wodzicki palace or the funerary monuments built in Poland and Moravia are also interesting. The article also presents an analysis of the stucco technique used by Baldassarre Fontana and a comparison with the construction site practices used in the Roman area.